Contributions to lichen diversity of Turkey from the Sarisu area (Kocaeli) - ÇOBANOĞLU, GÜLŞAH (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2013)
A total of 85 lichen taxa from the Sarisu area of the district of Kandira in Kocaeli Province were listed. Three new records for the biota of Turkey, Coenogonium pineti (Ach.) Lucking & Lumbsch, Lecania cuprea (A. Massal.) Van den Boom & Coppins, and Opegrapha calcarea Turner ex Sm., have been identified within the context of this study along with 81 new taxa for the province of Kocaeli.
Keywords: Lichenised fungi; biodiversity; biota; Kocaeli